2009
DOI: 10.1111/j.1469-7580.2009.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of paleontological and molecular data in supertrees for comparative studies: the example of lissamphibian femoral microanatomy

Abstract: A new method to assemble time-calibrated supertrees is able to incorporate paleontological and molecular dates. This method, along with new branch length transformations, is implemented in the Stratigraphic Tools for Mesquite. It was used here to analyse a dataset on bone microanatomy, body size and habitat of 46 species of lissamphibians through a variety of methods (Felsenstein independent contrasts, variance partition with phylogenetic eigenvector regression, discriminant analyses and simple regressions). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 63 publications
2
39
0
Order By: Relevance
“…This implied that the larger nodal values were associated with unusually high contrasts, i.e. taxa with higher character values systematically evolve faster (the opposite situation to the example given in Laurin et al. (2009)).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…This implied that the larger nodal values were associated with unusually high contrasts, i.e. taxa with higher character values systematically evolve faster (the opposite situation to the example given in Laurin et al. (2009)).…”
Section: Methodsmentioning
confidence: 95%
“…Further, preliminary analyses showed that differences between ML and independent contrasts ancestor values are small and the overall magnitude of the values and relative relationships are comparable; there are no significant differences between the ancestor values estimated by the two methods. Regardless of which method is employed, accurate branch durations are important (Laurin, 2004; Laurin et al. , 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach to time-scaling the phylogeny results in many zero-length internal branches (Bapst 2013). As has been commonly done in other molecular and morphological studies (e.g., Laurin et al 2009;Hopkins 2011), we add a small, arbitrary amount of time (0.01 Myr) to all zero-length branches in the terebratulide tree. We obtained radiometric ages of stage boundaries from the revised Devonian timescale of Ogg et al (2009).…”
Section: Phylogenetic Frameworkmentioning
confidence: 99%
“…Osteosclerosis observed in the histotypes IV may be produced by bone mass increase, which results in heavy, dense bone typical of slow swimmers living in shallow water Houssaye, 2009;Laurin et al, 2009;Laurin et al, 2011;Ricqlès and Buffrénil, 2001). The spongy condition present in the histotypes V is characteristic of open marine active swimmers (Houssaye et al, 2013(Houssaye et al, , 2014Ricqlès and Buffrénil, 2001).…”
Section: The Origin Of the Variabilitymentioning
confidence: 99%